Information Bank on African Development Studies (IBADS) - Raheem, Ghazali (World Bank, Washington, DC, 2012)
In achieving the multiple objectives of increasing Africa's access to information, strengthening its research and policymaking capacity, and narrowing the technology gap between Sub-Saharan Africa (SSA) and other developing regions, the World Bank (through its Africa Technical Department, and Information Solutions Group Department) has set up the Information Bank on African Development Studies (IBADS) to make the Bank's information on Africa electronically accessible. The note describes IBADS, as an electronic mailing service to disseminate information about development studies on SSA. It contains data archives of abstracts of studies, which are electronically retrieved, and mailed to a requestor over the global INTERNET. The service will be expanded to include full-text reports, and relevant development studies undertaken by other units of the Bank, as well as academic, and research institutions worldwide. The note further describes how to access IBADS, how to become a subscriber, and how to include an abstract under IBADS.